A-bar Dependency, Wh-scrambling in Korean, and Referential Hierarchy - Lee, Gunsoo (Kansas Working Papers in Linguistics, 1996)
'There is an argument-adjunct asymmetry in wh-extractions from weak islands. Some previous approaches to the issue concur that the reason why argument wh-phrases may create long distance A' dependencies across the islands is due to their referential properties. while non-referential adjunct wh-phrases must establish A' dependencies inside some local domain. The notion of referentiality that my analysis crucially employs, unlike the previous approaches, is defined by a set theory. This set theoretic notion of referentiality establishes a referential hierarchy among different wh-phrases, and this hierarchy correlates with the different degrees of strength in A' dependencies that different wh-phrases show in their extractions across weak islands.